2012
DOI: 10.1161/hypertensionaha.112.196949
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cardiovascular Rhythmicity in Children Born Small for Gestational Age

Abstract: Abstract-Low birth weight is frequently associated with a disproportionately high incidence of cardiovascular disease, diabetes mellitus, and kidney disease in adulthood. Epidemiological studies have identified an inverse association between low birth weight or being small for gestational age and hypertension in adulthood. We hypothesized that children born with low birth weight might have altered circadian and ultradian cardiovascular rhythmicity independent of the prevailing blood pressure level. Twenty-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 36 publications
2
21
0
2
Order By: Relevance
“…Interestingly, these authors found that the changes in cardiovascular rhythmicity correlated with changes in visceral obesity, indicating that visceral fat plays an important role in the sympathetic activity of adolescents with HTN [41]. The predisposition to alterations in BP rhythmicity may even be congenital or acquired early in child's development as documented by the decreased nocturnal dipping and decreased amplitudes in children born small for gestational age and then evaluated at the age of 8 years [42]. These alterations in BP rhythmicity were observed independently from the presence of HTN.…”
Section: Bp Rhythmicitymentioning
confidence: 99%
“…Interestingly, these authors found that the changes in cardiovascular rhythmicity correlated with changes in visceral obesity, indicating that visceral fat plays an important role in the sympathetic activity of adolescents with HTN [41]. The predisposition to alterations in BP rhythmicity may even be congenital or acquired early in child's development as documented by the decreased nocturnal dipping and decreased amplitudes in children born small for gestational age and then evaluated at the age of 8 years [42]. These alterations in BP rhythmicity were observed independently from the presence of HTN.…”
Section: Bp Rhythmicitymentioning
confidence: 99%
“…Low birth weight (and catch-up growth after birth) and adverse intrauterine conditions (e.g., preeclampsia) have been well-established etiologies for high BP in childhood [42–45]. Birth weight is a complex multifactorial trait itself with heritability around 20–30 % [4649].…”
Section: Influence Of Other Family Risk Factors On Familial Aggregatimentioning
confidence: 99%
“…Because substantial development of the autonomic nervous system (ANS) occurs during the third trimester of pregnancy (Van Leeuwen, Lange et al, 1999), ANS functioning may be altered in individuals born prior to 28 weeks of gestation. Indeed, preterm birth has been linked to alterations in the development of the vasculature (Norman, 2008), ANS functioning (Yiallourou, Witcombe, et al, 2013), and cardiac rhythmicity (Wolfenstetter, Simonetti et al, 2012). Preterm birth also has been associated with higher blood pressure in adults (Bergvall, Iliadou et al, 2007; Dalziel, Parag et al, 2007) and lower heart rate variability (HRV) in children (Rakow, Katz-Salamon et al, 2013), especially if the children experienced growth-restriction in utero (Schneider, Fiedler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%